The Influence of Key Performance Indicators (KPIs) on Employee Performance and Company Productivity at PT Nogopatmolo Banjarmasin - Noor Syifa Hayati; Teguh Wicaksono; Abdurrahim Abdurrahim (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to examine: (1) the influence of Key Performance Indicators (KPIs) on employee performance at PT Nogopatmolo Banjarmasin, (2) the influence of employee performance on company productivity at PT Nogopatmolo Banjarmasin, (3) the influence of KPIs on company productivity at PT Nogopatmolo Banjarmasin, and (4) the influence of KPIs on company productivity through employee performance as a mediating variable. This research employed a quantitative approach. The population consisted of all employees at PT Nogopatmolo Banjarmasin, totaling 120 individuals. A sample of 54 respondents was selected using the Slovin formula. Primary data were collected through interviews and questionnaires, while secondary data were obtained through documentation studies. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the SmartPLS 3.0 application. The results of the study indicate that: (1) KPIs have a positive and significant effect on employee performance at PT Nogopatmolo Banjarmasin, (2) employee performance has a positive and significant effect on company productivity, (3) KPIs have a positive and significant effect on company productivity, and (4) KPIs have a positive and significant effect on company productivity through employee performance as a mediating variable. These findings suggest that the proper implementation of KPIs can enhance employee work quality and sustainably boost company productivity. A single paragraph, maximum 250 words. Abstract content must contain (1) an overview of the object of research, (2) problems, and research objectives, (3) proposed methods, (4) main findings and results and synthesis of main ideas, and (5) conclusions.